Representações das práticas e práticas das representações : um estudo com psicólogos e usuários dos CRAS de Sergipe. - Sobral, Marcela Flores Cardoso (2011)
This work analyses the relationship between social representations and social practices, with a focus on the psychologist‟s professional activity in a specific and recent context: that of the Centros de Referência de Assistência Social CRAS (Social Assistance Reference Centres). Specifically, we investigate both the social representations psychologists have of the centres‟ users as well as those users have towards psychologists and their relationship with the practices of these professionals in Sergipe‟s CRASs. In order to accomplish this, two studies were carried out: one with 27 psychologists working in CRASs; and another with 20 users of this service. In the first study, we used a questionnaire and, in the second, a structured interview. The results revealed, in the first study, dissociation between what the professionals declared their practices to be and the perception of such practices from other psychologists‟ perspectives, which allowed us to infer the real practice adopted by psychology professionals. We perceived, in addition, that subjects that have a more psychologising representation of their users exhibit greater coherence between representations and practices as well as more negative views in regards to work in the CRAS. In the second study, it was possible to demonstrate that the representation of psychology, even in different contexts of exercise, is still associated to a psychologist‟s role in the clinical area, as a solver of psychopathologic problems and as having conversation, guidance, and counsel as their fundamental practices. Such representations are related to both user perceptions of the psychologists‟ practices as well as with real practices adopted by the CRAS psychologists. These results are discussed in light of the Theory of Social Representations and their relationships with social practices.